Recycling of Poly(Propylene) Based Car Bumpers in the Perspective of Polyolefin Nanoclay Composite Film Production - Nemr El Hajj; Sylvain Seif; Nancy Zgheib (Recycling)
This study uses the melt compounding method to recycle polypropylene-based car bumper waste (PP-CBW) in order to produce nanocomposite films for mulch application. The nanocomposite films were compounded by mixing virgin linear low-density polyethylene (LLDPE) with PP-CBW at a constant ratio of 4:1 in the presence of different percentages of nanofillers. Nanocomposites reinforced with nanoclays were compatibilized with an anhydride grafted polyethylene (PE-g-MAH), at a constant compatibilizer-to-clay ratio equal to 3, to improve the adherence between the nonpolar matrix and the hydrophilic nanoclay and acrylic paint present in the car bumper. An extruder with a corotating twin screw was used to produce blends of different compositions. To create nanocomposite films, the mixtures were further processed in a blown film extruder. The effect of the presence of nanoclays on the barrier, thermal, and mechanical properties of the nanocomposite films was investigated. The dispersion of clay layers in the matrix was examined by atomic force microscopy (AFM). The results indicate that 3 wt% of clay loading maximized the tensile strength in the transverse direction (TD) and machine direction (MD). A 1 wt% clay loading increased the MD tear resistance by 66% and manifested an optimum dart impact strength. Significant improvements in thermal and barrier properties were also achieved in the presence of 3 wt% clay loading.